Surgical removal of a sewing needle penetrated through the foramen lacerum into a canine brain. (9th June 2021) - Abed Alla, S.; Locatelli, A.; Losio, S.; Allevi, G.
Abstract : An intracranial metallic foreign body (sewing needle) was diagnosed in an 11‐month‐old Cavalier King Charles Spaniel. Clinical evaluation showed drooling and chewing, but an otherwise normal neurological examination. Skull radiographs showed a metallic foreign body extending from the pharynx into the skull. A CT scan confirmed the presence of a foreign body crossing the right foramen lacerum into the brain. The needle was removed surgically with the aid of fluoroscopy. No complications were noted, except for transient right Horner's syndrome, most likely due to partial damage of the sympathetic postganglionic fibres that lie in the region of the tympanic bulla following surgery. The owner reported the dog being healthy 3 months after surgery.